"Stash-IS" noliktavas informāciju sistēma - Riekstiņš, Eduards (Latvijas Universitāte, 2023)
Šajā kvalifikācijas darbā tika izstrādāta “Stash-IS” noliktavas informāciju sistēma, kas ir paredzēta maziem uzņēmumiem celtniecības vai remontdarbu sfērā. “Stash-IS” informāciju sistēma ļauj tās autorizētajiem lietotājiem pārvaldīt noliktavu preces un piesaistīt tās projektiem, kā arī sistēmai ir sava publicēšanas funkcionalitāte sistēmas lietotāju savstarpējai saziņai. “Stash-IS” informāciju sistēma ir balstīta uz īstas informāciju sistēmas pamata, ar kuru strādāts prakses laikā. Tā ir izveidota ar Ruby on Rails ietvaru, tāpēc sistēma izstrādāta atbilstoši Ruby on Rails izstrādes principiem - Don't Repeat Yourself: DRY un Convention Over Configuration.

In this qualification thesis, the "Stash-IS" warehouse information system was developed, and it is intended for small companies in the field of construction or repair work. The "Stash-IS" information system allows authorized users to manage warehouse items, attach them to projects, the system also has its own publishing functionality for mutual communication between system users. Using this system, it’s users will be able to organize projects and products. The "Stash-IS" information system is based on a real information system, which was worked with during the internship. It is created with Ruby on Rails framework, so the system was developed according to Ruby on Rails development principles - Don't Repeat Yourself: DRY and Convention Over Configuration .
"Stash-IS" warehouse information system
Keywords: Datorzinātne; Informāciju sistēma; tīmekļa lietotne; Ruby on Rails; remontdarbi; celtniecība